Effects of lead, cadmium, copper and zinc levels on the male reproductive function. (4th July 2021) - Chabchoub, Ines; Nouioui, Mohamed Anouar; Araoud, Manel; Mabrouk, Mahmoud; Amira, Dorra; Ben Aribia, Mohamed Habib; Mahmoud, Khaled; Zhioua, Fethi; Merdassi, Ghaya; Hedhili, Abderrazek
Abstract: This study aimed to investigate the effects of heavy metals on measures of male fertility. One hundred and two infertile men with occupational exposure and thirty fertile men were included in this study. Blood and urinary levels of lead, cadmium, zinc and copper were measured by atomic absorption spectrophotometry. Semen parameters and a motile sperm organelle morphology examination were also performed. Measures of hormonal levels, oxidation–reduction potential, DNA fragmentation index and chromatin condensation were assessed for all participants. Heavy metals levels, oxidative stress and DNA quality were significantly higher in the infertile group compared to controls. FSH and testosterone levels were lower in the infertile group. A urinary cadmium level was positively associated with abnormal sperm morphology ( r = .225, p < .05). Normal morphology was inversely correlated with the duration of the exposure ( r = −.227, p = .022). The blood lead level was positively related to the level of testosterone ( r = .223, p = .031). Cadmium and lead blood levels were positively correlated with the level of chromatin decondensation ( r = .528, p < .001; r = .280, p = .017). Our study showed that occupational exposure to heavy metals is very harmful to reproductive health. DNA quality and oxidative stress investigations must be recommended for reprotoxic exposed patients prior to in vitro fertilisation treatment.